USE OF TASK-CENTERED SYSTEM DESIGN IN THE INTERFACE DESIGN OF THE POPULATION DEMOGRAPHIC DATA INFORMATION SYSTEM - Muhammad Azmi Zaky; Allsela Meiriza; Dinda Lestarini; Pacu Putra; Nabila Rizki Oktadini (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2025)
Abstract: The rapid development of information and communication technology has prompted the government to provide digital-based services, including in the management of demographic data. This study aims to apply the Task-Centered System Design (TCSD) method in designing the Muara Enim Regency Demographic Data Information System. The TCSD method was chosen to ensure that the prototype design process was systematic and focused on user needs and tasks. The research stages included identification, user-centered needs analysis, scenario-based design, and walkthrough evaluation. The designed prototype supports several main tasks, including viewing demographic statistics, searching for specific data, submitting data download requests, and contacting the admin. The evaluation was conducted through online usability testing using the Maze platform with the System Usability Scale (SUS) instrument involving 13 respondents. The evaluation results showed an average SUS score of 78.5, which falls into the “good” category. This confirms that the interface design has met usability standards, is user-friendly, and is capable of supporting user needs in accessing and managing demographic data. Thus, the application of the TCSD method has proven to be effective in producing an interface design that is focused on user tasks and can be the basis for further system development. Keywords: system usability scale; task centered system design; user interface